2018
DOI: 10.1002/cpe.5077
|View full text |Cite
|
Sign up to set email alerts
|

A possibilistic framework for the detection of terrorism‐related Twitter communities in social media

Abstract: Summary Since the appearance of social networks, there was a historic increase of data. Unfortunately, terrorists are taking advantage of the easiness of accessing social networks and they have set up profiles to recruit, radicalize, and raise funds. Most of these profiles have pages that exist as well as new recruits to join the terrorist groups, see, and share information. Therefore, there is a potential need for detecting terrorist communities in social networks in order to search for key hints in posts tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 66 publications
0
17
0
Order By: Relevance
“…At this stage, the most serious social, political, legal, and ethical issues relating to information technology will begin to surface on a large scale. Consistent with Moor's assertion, the use of the Internet by extremists to disseminate propaganda and engage in other illegal online activities has since surfaced [13,[23][24][25][26][27][28].…”
Section: Literature Reviewmentioning
confidence: 98%
See 1 more Smart Citation
“…At this stage, the most serious social, political, legal, and ethical issues relating to information technology will begin to surface on a large scale. Consistent with Moor's assertion, the use of the Internet by extremists to disseminate propaganda and engage in other illegal online activities has since surfaced [13,[23][24][25][26][27][28].…”
Section: Literature Reviewmentioning
confidence: 98%
“…It contributes to the difficulty of policing activities that occur largely unregulated on the platform. Consider YouTube; despite community guidelines and administrative efforts, the platform maintains a massive archive of malicious and offensive videos [1,21,24,31,32]. Many of these videos remain online in the absence of a YouTube reviewer's flag request.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Thus, it is observed that deep learning techniques are better than machine learning algorithms in performance without using explicit feature extraction methods. The classification of extremism texts is either in binary [29][42] [43] or tertiary [35][47] [49] classes. These classes are 'extremist'-'non-extremist' [42], 'hate'-'non-hate' [50], etc.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition to centrality-based measures, some researchers proposed learning-based methods [11,[39][40][41][42][43] in recent years to identify the key actors in terrorist networks. Johnston and Weiss [39] designed an approach that can automatically identify the related web pages and text content to Sunni extremist propaganda on social media, where a deep neural networkbased model is used to classify propaganda content from other social media content.…”
Section: Related Workmentioning
confidence: 99%